What Is The Relationship Between Job Stress and Work fatigue Among Construction Workers? A Cross-Sectional Study - Fitri, Rika Yulianti; Budiyanto, Tri (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Job fatigue is the leading cause of job-related accidents and illnesses among construction worker who operate in physically and psychologically demanding situations. Job stress is one of the elements that contribute to job fatigue. Job stress and work fatigue-related emotional symptoms significantly influence worker job satisfaction. This study aimed to discover the link between job stress and fatigue in construction worker. A cross-sectional study design was employed for the research, with 30 participants drawn using the total sampling methodology. This type of primary data was gathered by distributing questionnaires in April 2023. Work stress was evaluated using the Work Stress Diagnostic Survey questionnaire in line with Permenaker No. 5 of 2018, while work Fatigue was measured using the IFRC's Subjective Self Rating Stress questionnaire. The frequency distribution test was used to examine data univariately, while the Chi-Square test was used to analyze data bivariately. The findings revealed that the majority of respondents (63.3%) had a low level of fatigue, with the variables related to work fatigue being quantitative overload (p=0.009) because workers need to carry out measurements and mark exact locations, and project managers need to calculate the estimated time for various stages of work, and career development with (p=0.047) because the construction sector has a rigid structure, where promotion is seen as a result of education and work experience There is no correlation between job fatigue and role ambiguity, role conflict, qualitative overload, and obligation to others. It was shown that quantitative overload and professional advancement are linked to fatigue in construction workers.